Analysis of production, consumption and environmental burden of plastic industry in Vietnam by input-output table - Thi Yen Ta; Thi Anh Tuyet Nguyen; Hoang Thi Hong Van (Vietnam Journal of Science, Technology and Engineering, 2021)
The plastic industry is an economic sector that plays an important role in promoting a circular economy in Vietnam. This study used the updated 2018 input-output (IO) table to identify and analyse the production and consumption of seven different plastics including: HDPE, PS, PE, PET, PVC, PP, and others. The study also integrated the IO model to unveil the environmental burden of these plastics through the plastic demand of 40 economic sectors and households. As a result, in 2018, the amount of direct solid waste from the plastic industry was 58,147 tons and the amount of indirect solid waste from the plastic industry to other economic sectors and the household sector were 214,258 tons and 6,262 tons, respectively. Agriculture and its services, food processing, fashion manufacturing, basic chemical production, electrical and electronic equipment production, and transport production embodied the highest indirect burdens due to their use of plastic products. This study contributes to MFA research and developing strategies for sustainable production and consumption of plastics and the management of plastic waste in Vietnam.